MEMAKNAI 1 TIMOTIUS 4:12-16 SEBAGAI DASAR PAK PERGURUAN TINGGI UMUM - Bintahan Marodjahan Harianja (Jurnal Christian Humaniora, 2020)
This article is an attempt to get a style of Christian Religious Education in Public Colleges with pluralist insights. Christian Christian Education in Indonesia should be rooted and live in the context of a pluralistic Indonesian society, and must be able to communicate the word of God in accordance with the pluralistic scope of Indonesian-ness. This paper departs from the struggle over the direction of religious education which has become increasingly exclusive or closed in recent times, and that is certainly not what is needed by Indonesia. One effort that can be done is to reinterpret sacred texts which can be the basis of religious education with a pluralist perspective, in this case the text of 1 Timothy 4: 12-16. This text appears in the plural Ephesus community where the church leader named Timothy ministered. Critical interpretation produced the message that Paul wanted Timothy to be able to dialogue the Gospel without having to avoid the differences that were characteristic of the city of Ephesus. Christian teaching must be able to make every student aware that they are part of the diversity.Key Words: Christian Religious Education, General Higher Education, Pluralism, 1 Timothy 4: 12-16